RNAi of a Putative Grapevine Susceptibility Gene as a Possible Downy Mildew Control Strategy - Marcianò, Demetrio; Ricciardi, Valentina; Marone Fassolo, Elena; Passera, Alessandro; Bianco, Piero Attilio; Failla, Osvaldo; Casati, Paola; Maddalena, Giuliana; De Lorenzis, Gabriella; Toffolatti, Silvia Laura (Frontiers in Plant Science, 2021)
Downy mildew, caused by the oomycete Plasmopara viticola, is one of the diseases causing the most severe economic losses to grapevine (Vitis vinifera) production. To date, the application of fungicides is the most efficient method to control the pathogen and the implementation of novel and sustainable disease control methods is a major challenge. RNA interference (RNAi) represents a novel biotechnological tool with a great potential for controlling fungal pathogens. Recently, a candidate susceptibility gene (VviLBDIf7) to downy mildew has been identified in V. vinifera. In this work, the efficacy of RNAi triggered by exogenous double-stranded RNA (dsRNA) in controlling P. viticola infections has been assessed in a highly susceptible grapevine cultivar (Pinot noir) by knocking-down VviLBDIf7 gene. The effects of dsRNA treatment on this target gene were assessed by evaluating gene expression, disease severity and development of vegetative and reproductive structures of P. viticola in the leaf tissues. Furthermore, the effects of dsRNA treatment on off-target (EF1α, GAPDH, PEPC and PEPCK) and jasmonic acid metabolism (COI1) genes have been evaluated. Exogenous application of dsRNA led to significant reductions both in VviLBDIf7 gene expression, five days after the treatment, and in the disease severity when artificial inoculation was carried out seven days after dsRNA treatments. The pathogen showed clear alterations to both vegetative (hyphae and haustoria) and reproductive structures (sporangiophores) that resulted in stunted growth and reduced sporulation. Treatment with dsRNA showed signatures of systemic activity signatures and no deleterious off-target effects. These results demonstrated the potential of RNAi for silencing susceptibility factors in grapevine as a sustainable strategy for pathogen control, underlying the possibility to adopt this promising biotechnological tool in disease management strategies.